The influence of the promotional mix with the application of integrated marketing instruments in the implementation of corporate branding strategies in function of competitive positioning of the brand - Valentina Mucunska Palevska; Sashko Gramatnikovski; Angela Milenkovska Klimoska (UTMS Journal of Economics, 2023)
This paper interprets and analyzes the innovative paradigm of creating and applying a strategic concept and approach to branding and brand communication. The modern business environment affirms the need for continuous research and analysis of current trends in business in order to create and implement efficient branding strategies, supported by a promotional mix of integrated marketing communication instruments. Branding strategies implemented through integrated marketing communication tools are fundamental to effective brand positioning and customer relationship management. According to the standards and values of the scientific-research public, the focus of interest of companies should be customers whose needs, attitudes and interests are distinctly sophisticated, which generates the need to adapt the corporate business process to the individual needs and expectations of each customer separately, which means that the content of the messages should be personalized to reach them and influence the creation or strengthening of brand awareness. Based on scientific knowledge, this paper, using analytical methodological research, confirms the correlation and proves that creating and implementing brand strategies using integrated marketing communication instruments is a prerequisite for successful brand positioning and sustainability of brand competitiveness.
Keywords: M31; M37; 330; brand; strategies; integrated marketing communications; competitiveness; sustainability